Exploring Research Practices in EFL Classrooms: Perspectives of Secondary-Level Teachers - Neupane, Ram Nath (Voice: A Biannual & Bilingual Journal, 2024)
Research is a systematic investigation to find a solution to a problem. The present study attempts to explore the practices of research activities in English language classrooms. To accomplish this, data were purposefully collected from seven secondary-level English teachers of Palpa through semi-structured interviews. The gathered data were subsequently transcribed, coded, and analyzed thematically, categorizing them into seven distinct topics. The findings suggest that research acts as a fundamental source of knowledge for both teachers and students. Teachers mainly use observation checklists, questionnaires, and interview guides as classroom research tools. Nearly all permanent teachers engage in action research, while temporary teachers refrain from participating in research activities due to the perceived lack of relevance to their job promotion. Teachers tend to use both formal and informal approaches in their research activities. Conducting research in the classroom is essential, as it promotes interaction, collaboration, and critical thinking skills among students. This study may be valuable for those interested in incorporating research activities into English language classrooms.